Global trends of research on tuberculous pleurisy over the past 15 years: A bibliometric analysis - Bian, Yiding; Deng, Mingming; Zhang, Qin; Hou, Gang (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculous pleurisy (TP) is a common type of extrapulmonary tuberculosis (EPTB). With the development of research and changes in TP patient characteristics, an increasing number of studies have revealed the prevalence, risk factors, and novel diagnosis techniques. Thus, this bibliometric analysis was performed to identify global scientific output characteristics and research hotspots and frontiers for TP over the past 15 years. We searched the Web of Science Core Collection (WoSCC) Science Citation Index Expanded (SCI-expanded) for literature published between 2007 and 2021 and recorded their information. The Bibliometrix software package was used for bibliometric indicator analysis, and VOSviewer was used to visualize the trends of and hotspots in TP research. A total of 1,464 original articles were reviewed, and the results indicated that the annual number of publications (Np) focusing on TP has increased over the past 15 years. China had the largest number of papers and the highest H-index, and the United States ranked first for number of citations (Nc). EGYPTIAN KNOWLEDGE BANK and PLOS ONE were the most prolific unit and journal, respectively. The use of the Xpert assay and immune-related biomarker detection to diagnose TP appears to be a recent research hotspot. This bibliometric study demonstrated that the number of publications related to TP have tended to increase. China is a major producer, and the United States is an influential country in this field. Research in the past 15 years has been predominantly clinical research. The diagnosis of TP was the focus of research, and the exploration of novel diagnostic techniques, verification of diagnostic markers, and combination of diagnostic methods have been recent research hotspots. Immune-related biomarkers should be given more attention in the field of TP diagnosis.